Preface - Zainol, Rosilawati (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
This issue brings together four articles covering a wide spectrum from the importance of mutual undestanding and dialogue, the understanding of the cosmic symptoms, Sīrah to efforts in reducing carbon emission in Malaysia.